Wage inequality and firm growth - Holger M. Mueller; Paige P. Ouimet; Elena Simintzi (Luxembourg Income Study (LIS), 2015)
We examine how within-firm skill premia-wage differentials associated with jobs involving different skill requirements-vary both across firms and over time. Our firm-level results mirror patterns found in aggregate wage trends, except that we find them with regard to increases in firm size. In particular, we find that wage differentials between high- and either medium- or low-skill jobs increase with firm size, while those between medium- and low-skill jobs are either invariant to firm size or, if anything, slightly decreasing. We find the same pattern within firms over time, suggesting that rising wage inequality - even nuanced patterns, such as divergent trends in upper- and lower-tail inequality - may be related to firm growth. We explore two possible channels: i) wages associated with "routine" job tasks are relatively lower in larger firms due to a higher degree of automation in these firms, and ii) larger firms pay relatively lower entry-level managerial wages in return for providing better career opportunities. Lastly, we document a strong and positive relation between within-country variation in firm growth and rising wage inequality for a broad set of developed countries. In fact, our results suggest that part of what may be perceived as a global trend toward more wage inequality may be driven by an increase in employment by the largest firms in the economy.
Keywords: 330